QPI Allows in vitro Drug Screening of Triple Negative Breast Cancer PDX Tumors and Fine Needle Biopsies - Murray, Graeme F.; Turner, Tia H.; Guest, Daniel; Leslie, Kevin A.; Alzubi, Mohammad A.; Radhakrishnan, Senthil K.; Harrell, J. Chuck; Reed, Jason (Frontiers in Physics, 2019)
The development of resistance to initially successful cancer therapies is a major cause of the morbidity and mortality associated with cancer. Identifying evolving resistance at an early stage could inform clinical decision making to adapt therapies before resistant cancer cell phenotypes have become clonally dominant or metastasized. This goal of early detection has prompted heavy investments in liquid biopsy, organoid, and high-throughput screening methodologies. Recently, High-Speed Live-Cell Interferometry (HSLCI), a quantitative phase imaging (QPI) methodology, was shown to predict triple-negative breast cancer (TNBC) patient-derived xenograft (PDX) sensitivity to carboplatin only 40 h after tumor removal from a mouse. In this paper we discuss barriers to applying HSLCI to therapy selection in human TNBC patients, and present preliminary results addressing some of those barriers. Our results include engineering improvements to increase sample throughput and demonstrating that HSLCI can measure drug response of agents with a variety of mechanisms of action. Finally, we show proof of concept data for direct testing of samples obtained from minimally invasive, fine needle biopsies.